PHRASEOLOGICAL UNITS REFLECTING HUMAN EXPERIENCE: A LINGUISTIC ANALYSIS - Shamshetova Raushan, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Summary: This article examines a selection of English phraseological units with a focus on expressions that reflect universal human experiences, such as determination, perception, and personal conduct. The study investigates the grammatical structure, etymology, semantic characteristics, and contextual usage of three phrases: "In the long run", "Take heart", and "Bear in mind". Through literary examples and linguistic analysis, the article demonstrates how these fixed expressions contribute to expressive communication and enrich the vocabulary of English language learners.